In vitro regeneration of two high-yielding eggplant (Solanum melongena L.) varieties of Bangladesh - Tanzena Tanny, Sabina Yesmin, Mst Muslima Khatun,; Protity, Anica Tasnim; Salimullah, Md; Alam, Iftekhar (Current Botany)
An in vitro regeneration protocol was developed for two high-yielding eggplant varieties (Solanum melongena L.) namely BARI begun-4 and BARI begun-6. Multiple shoots were regenerated from cotyledonary explants through organogenesis with growth regulators of different combinations and concentrations. The best response towards multiple shoot regeneration was achieved from cotyledon explants on MS media complemented with 1 mg/l BAP + 0.2 mg/l IAA in both the two varieties of eggplant. Elongation of shoots was achieved on hormone free MS medium. Regenerated shoots of both the varieties produced active in vitro root system on half strength of MS medium supplemented with 0.2 mg/l IBA. The in vitro grown plantlets were acclimatized in soil, grew up to maturity, flowered, fruited and produced seeds as normal healthy plant like the control.